EMPLOYEE BEHAVIOR IN THE FACE OF COVID-19: STRESS AND COPING MECHANISM - Paul Joy Onyinye (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study investigated the psychological state of employees under the COVID-19 pandemic, the attendant job stress and corresponding coping mechanisms adopted to remain sustainable. The pandemic situation brought operating difficulties and challenges to many industries around the world, and organizational managers are challenged to have the ability to adapt to disasters and recover from such emergencies. We found that through the factors of the organizational culture, the abilities to organize and manage operations, the adaptation capacity as well as coping mechanisms of the organizations affects the development of organizational resilience and consequently sustainability of businesses. Workplace stress is bound to happen more regularly as there may be many stressors in life which range from personal to work-related especially as imposed by the outbreak of COVID-19 pandemic; therefore, it is recommended for modern organizational managers that there should be social support coming from the workplace as integral in helping the employees cope with stress of such nature.